Covid-19 z perspektywy chrześcijańskiej - Urbina, César Izquierdo (Warszawskie Studia Teologiczne, 2020)
This article is an intellectual attempt to deal with the consequences of the multifaceted crisis caused by the Covid-19 pandemic. It is based on the principles of Catholic doctrine. First, an attempt is made to answer the question about the the[1]ological significance of the crisis itself: can it be understood in the key of “God’s pu[1]nishment”, as it is often done in statements and publications referring to the Catholic point of view? Then, the spiritual consequences of the crisis are presented, first of all the impact of isolation on interpersonal relationships and the potential effects it may have on a people’s ability to be open to transcendence. Finally, on the base of the Catholic social teaching, postulates are formulated regarding the necessary modifications in the lifestyle and principles of the global economy, so that the drama of the pandemic may become an opportunity for greater humanization and a step on the way to conversion of human society